Energy Yield of Tracking PV Systems in Jordan - A. Al Tarabsheh; I. Etier; A. Nimrat (International Journal of Photoenergy)
This paper analyzes the energy yield of photovoltaic (PV) modules mounted on fixed tilt, one-axis, and two-axis tracking system towards maximizing the annual energy production. The performance evaluation of the proposed design of the tracking systems is carried via simulating the global radiation averages using METEONORM software and depicting the simulation results in figures using MATLAB software. The one-axis system is simulated by either fixing the azimuth angle while optimizing the inclination angles or fixing the inclination angle while optimizing the azimuth angles; simulation results show an increase in energy yield of 5.87% and 20.12% compared to that of fixed tilt system, respectively. In the two-axis system, optimization of both azimuth and inclination angles is carried out simultaneously which resulted in 30.82% improvement in energy yield. Therefore, 30% improvement in energy yield is directly reflected as saving in PV system cost due to reduction of the PV modules surface area.